Role of frozen section biopsy in the diagnosis of ovarian masses - Jolly, Rabeya Sultana; Chowdhury, Mina; Amin, Rogina; Elora, Ashfi Laila; Afrose, Taslima; Kader, Mousumi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Ovarian malignancy is an important cause of mortality among women with most cases being diagnosed late and requiring aggressive management. The association between the final diagnosis on standard conventional histopathological sections and the examination of intraoperative frozen sections is an important tool for quality control. Therefore, this study aimed to assess the role of frozen section biopsy in diagnosing ovarian masses. Methods: This was a cross-sectional study conducted in the department of obstetrics and gynecology, Dhaka Medical College Hospital, Dhaka, Bangladesh during the period from January 2020 to December 2020. In our study, we included 50 diagnosed cases of ovarian masses who attended the department of obstetrics and gynecology in Dhaka Medical College Hospital for surgery. Results: The mean age of the patients was 31.68±11.04 years. On the frozen section, forty-one patients (82%) were diagnosed as benign cases while nine patients (18%) were identified as malignant. The final histopathologic diagnosis revealed 38 (76%) as benign tumors and 12 (24%) as malignant tumors. Frozen section biopsy (FSB) was found to be 75% sensitive and it showed 100% specificity. The PPV, NPV, and diagnostic accuracy of FSB were found to be 100%, 92.6%, and 94% respectively. Among the three discordant cases, two were mucinous adenocarcinoma and one was papillary serous cyst adenocarcinoma. Conclusions: This study showed a diagnostic accuracy of 94%, which is an eye-opener for gynecological oncologists regarding the usefulness of frozen section biopsy. Frozen section diagnoses can be extremely helpful in the clinical management of ovarian cancers.